Impact of resistance mutations on efficacy of dolutegravir plus rilpivirine or plus lamivudine as maintenance regimens: a cohort study. (March 2022) - Gagliardini, Roberta; Baccini, Michela; Modica, Sara; Montagnani, Francesca; Zanelli, Giacomo; Borghetti, Alberto; Dreassi, Emanuela; Lombardi, Francesca; Pecorari, Monica; Borghi, Vanni; Callegaro, Annapaola; Micheli, Valeria; et al.
ABSTRACT: Objectives: The aim of this study was to evaluate the impact of resistance mutations on efficacy of dolutegravir-based two-drug regimens (2DR). Methods: Virologically suppressed patients with HIV-1 switching to dolutegravir + lamivudine or rilpivirine or to a dolutegravir-based three-drug regimen (3DR) with pre-baseline genotype were selected. Virological failure (VF) was defined as one HIV-RNA viral load (VL) >200 cps/mL or two consecutive VL >50 cps/mL; treatment failure (TF) was defined as VF or treatment discontinuation (TD). Resistance was defined as at least low-level resistance to at least one drug of the current regimen. Propensity score matching was used to conduct adjusted analyses within a competing risks framework. Results: A total of 971 dolutegravir-based regimens were selected: 339 (34.9%) 2DR and 632 (65.1%) 3DR. The adjusted cumulative 48-week incidence of VF was 4.2% (90% CI 3.1%–5.3%) with 2DR and 4.7% (90% CI 3.5%–5.8%) with 3DR. The cumulative 48-week incidence of TF was 15.8% (90% CI 13.9%–17.9%) with 2DR and 24.5% (90% CI 22.2%–27.0%) with 3DR. For VF, the estimated hazard ratio (HR) for 2DR vs. 3DR was 1.02 (90% CI: 0.78–1.34), with evidence of effect modification by low-level resistance (HR 3.96, 90% CI: 2.10–7.46). The estimated HR of TF for 2DR vs. 3DR was 0.54 (90% CI: 0.48–0.60). The 48-week cumulative incidence of TD was 11.7% (8.7%, 14.6%) in 2DR and 19.6% (16.9%, 22.4%) in 3DR. Conclusions: Dolutegravir-based 2DR showed high virological efficacy and durability; however, past resistance increased the risk of VF, but not of TD or TF.